The cnidarian nematocyst: a miniature extracellular matrix within a secretory vesicle - Özbek, Suat (Protoplasma, 2011)
Nematocysts are the taxon-defining features of all cnidarians including jellyfish, sea anemones, and corals. They are highly sophisticated organelles used for the capture of prey and defense. The nematocyst capsule is produced within a giant post-Golgi vesicle, which is continuously fed by proteins from the secretory pathway. Mature nematocysts consist of a hollow capsule body in which a long tubule is coiled up that, upon discharge, is expelled in a harpoon-like fashion. This is accompanied by the release of a toxin cocktail stored in the capsule matrix. Nematocyst discharge, which is one of the fastest processes in biology, is driven by an extreme osmotic pressure of about 150 bar. The molecular analysis of the nematocyst has from the beginning indicated a collagenous nature of the capsule structure. In particular, a large family of unusual minicollagens has been demonstrated to form the highly resistant scaffold of the capsule. Recent findings on the molecular composition of Hydra nematocysts have confirmed the notion of a specialized extracellular matrix, which is assembled during an intracellular secretion process to form the most complex predatory apparatus at the cellular level.